This problem has already been worked out for me, and I understand most of what is going on, but there is one part of it that I am confused about and not sure where exactly it came from. This is the problem:
Compute the following integral showing your work including the appropriate antiderivative. Hint: The final answer should be an integer.
∫[from 4 to 9] 2/((sqrt of y)*(1-sqrt of y)^2) dy
Step 1: u=1- sqrt of y
du=-1/(2*sqrt of y) dy
Step 2: y=4-->u=-1
Step 3: ∫[from -1 to -2] -4/u^2 dy
Step 4: 4/u |(from -1 to -2)
=(4/-2) - (4/-1) = 2
I pretty much understand everything that is going on in this problem except for the third step. I can't seem to figure out where the -4 came from. If anyone could explain to me where the -4 came from or how you would go about getting it, I would greatly appreciate it. Thanks in advance to anyone who can help.